Twelfth Five Year Plan 2012-2017 and Annual Plan 2012-2013 Volume II General Statements and Annexures - Planning Commission (Planning Commission, 2012)
Draft annual state plan 2012-13 proposed outlays draft annual state plan 2012-13 proposed outlays(from state budget) draft annual state plan 2012-13 proposed outlays (rural local bodies) draft annual plan - 2012-13 proposed outlays for state plan (scheme-wise) physical target and achievements statement regarding externally aided projects centrally sponsored schemes central sector schemes financial outlays / expenditure for voluntary sector women component (WC) in the state plan programmes
Planning Department Government of Meghalaya